MAIN REASONS BEHIND SHADOW ECONOMY - Stanikūnas, Rimantas (Ekonomika, 2012)
Abstract. The main goal of this sludy was to identify the main drivers of the shadow economy and to evaluate its impact on the collection of the state budget income. The paper tries to explain what factors affect the origination and development of the shadow economy. The main analysed factors include unemployment rate and the burden of taxation. Authors have made a three-way analysis including a correlation analysis, a review of the statistical, data and a sociological survey.The analysis has shown that there is no single factor to be considered as most significant for the shadow economy; is conditioned by a complex of related economic, legal and administrative, social, and psychological factors. The list of the most relevant factors is provided. In summary, the paper also provides the recommended approaches to fight the shadow economy.Key words: shadow economy, state budget income, unemployment, burden of taxation